PSYCHOSOMATIC FACTORS IN CARDIOLOGY, NEUROLOGY, AND JOINT DISEASES - Turdiyeva Muyassar Ernazarovna; Rustamova Yulduz Alisher qizi; Normatova Saida Sotiboldiyeva; Korjovova Mahliyo Norbekovna (Modern American Journals, 2025)
This article explores the intricate relationship between cardiovascular, neurological, and joint diseases with psychosomatic factors. It examines how stress, depression, anxiety, and emotional instability contribute to the development and progression of these diseases, particularly in the fields of cardiology, neurology, and rheumatology. The article highlights the physiological responses of the body to psychological states, such as increased heart rate, headaches, and joint inflammation, demonstrating the deep connection between the mind and body. Additionally, the article emphasizes the importance of integrating psychotherapy, stress management techniques, and emotional health recovery into the treatment of these conditions. The findings suggest that effective treatment requires not only pharmacological interventions but also psychological approaches to address the root causes of these diseases, fostering holistic healing.
Keywords: Psychosomatics, cardiology, neurology, joint diseases, stress, emotional health, cardiovascular system, nervous system, rheumatoid arthritis, psychotherapy, depression, anxiety, holistic approach.